(3hajGJ GdCYjGf hCfHGA CHfGA GdReGfs - (3GHf NdcGf , CMeO Hf eMeO Hf EHQGgje Hf CHj HcQ GdHQecj GdGQHdj, TeS GdOjf CHh GdYHGS,J (B681 (3g` s ((3YHOGddg Hf SdjeGf Hf eMeO Hf Ydi Hf eMeO GdRhQGfi s)
(3ChdgG (B:s
(3MQa GdTjf s
(3BNQgG (B:s
(3BNQ MQa GdaGA s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B220 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B59s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B327 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B37 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs